Estimating the epidemiological impact and cost-effectiveness profile of a nonavalent HPV vaccine in Spain - Jesús De La Fuente; Juan José Hernandez Aguado; María San Martín; Paula Ramirez Boix; Sergio Cedillo Gómez; Noelia López (Taylor & Francis Group, 2019)
Human papillomavirus (HPV) is one of the main causes of infection-related cancer. The bivalent vaccine (2vHPV) (16/18) and quadrivalent (6/11/16/18) HPV vaccine (4vHPV) have been included in the Spanish vaccination calendar since 2007. The new nonavalent HPV vaccine (9vHPV), approved in Europe in 2015, includes nine HPV types 6/11/16/18/31/33/45/52/58 and has been available in Spain since May 2017. Our study aims to estimate the epidemiological impact and the cost-effectiveness of a girls-only and a gender-neutral vaccination program with 9vHPV compared to the current vaccination program in Spain. A dynamic transmission model simulating the natural history of HPV infections was calibrated to the Spanish setting and applied to estimate costs and quality-adjusted life years (QALYs) associated with vaccination strategies using a payer perspective and a 100-year time horizon. A girls-only vaccination strategy at age 12 years with 9vHPV was found to be a cost-effective strategy compared with 4vHPV (incremental cost-effectiveness ratio (ICER) of €7,718 per QALY). Compared with girls-only vaccination with 4vHPV, gender-neutral vaccination with 9vHPV was associated with further reductions of up to 28.5% in the incidence of cervical intraepithelial neoplasia (CIN) 2/3 and 17.1% in the incidence of cervical cancer, as well as with a 14.0% reduction in cervical cancer mortality. Furthermore, a gender-neutral vaccination program with 9vHPV could potentially be cost-effective considering some parameters as head and neck protection or discount rates, leading to a reduction in the burden of HPV-related diseases in both sexes in the Spanish population.